Terrestrial ecosystems of the Antarctic Peninsula and their responses to climate change and anthropogenic impacts - Bargagli, R. (Ukrainian Antarctic Journal, 2020)
Antarctica and the Southern Ocean are unique natural laboratories where organisms adapted to extreme environmental conditions have evolved in isolation for millions of years. These unique biotic communities on Earth are facing complex climatic and environmental changes. Terrestrial ecosystems in the Antarctic Peninsula Region (APR) have experienced the highest rate of climate warming and, being the most impacted by human activities, are facing the greatest risk of detrimental changes. This review provides an overview of the most recent findings on how biotic communities in terrestrial ecosystems of the Antarctic Peninsula Region (APR) are responding and will likely respond to further environmental changes and direct anthropogenic impacts. Knowledge gained from studies on relatively simple terrestrial ecosystems could be very useful in predicting what may happen in much more complex ecosystems in regions with less extreme temperature changes. The rapid warming of the APR has led to the retreat of glaciers, the loss of snow and permafrost and the increase of ice-free areas, with a consequent enhancement of soil-forming processes, biotic communities, and food web complexity. However, most human activity is concentrated in APR coastal ice-free areas and poses many threats to terrestrial ecosystems such as environmental pollution or disturbances to soil communities and wildlife. People who work or visit APR may inadvertently introduce alien organisms and/or spread native species to spatially isolated ice-free areas. The number of introduced non-indigenous species and xenobiotic compounds in the APR is likely to be greater than currently documented, and several biosecurity and monitoring activities are therefore suggested to Antarctic national scientific programs and tourism operators to minimize the risk of irreversible loss of integrity by the unique terrestrial ecosystems of APR.